2018
DOI: 10.3390/molecules23020462
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Key Aroma Compounds in Proso Millet Wine Using Headspace Solid-Phase Microextraction and Gas Chromatography-Mass Spectrometry

Abstract: The volatile compounds in proso millet wine were extracted by headspace solid-phase microextraction (85 μm polyacrylate (PA), 100 μm polydimethylsiloxane (PDMS), 75 μm Carboxen (CAR)/PDMS, and 50/30 μm divinylbenzene (DVB)/CAR/PDMS fibers), and analyzed using gas chromatography-mass spectrometry; the odor characteristics and intensities were analyzed by the odor activity value (OAV). Different sample preparation factors were used to optimize this method: sample volume, extraction time, extraction temperature, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 33 publications
0
16
2
Order By: Relevance
“…Our previous study showed that benzaldehyde, acetophenone, cinnamaldehyde, trans-cinnamaldehyde and 2-phenyl-2-butenal were also classified as aromatics with benzene, and their typical floral and honey smelling was one of the big differences between the young and aged Chinese rice wine. 39 It was also reported that benzaldehyde was one of the most important aroma aldehydes in Proso Millet wine, 43 as a type of traditional Chinese yellow wine.…”
Section: Aldehydes and Ketonesmentioning
confidence: 98%
“…Our previous study showed that benzaldehyde, acetophenone, cinnamaldehyde, trans-cinnamaldehyde and 2-phenyl-2-butenal were also classified as aromatics with benzene, and their typical floral and honey smelling was one of the big differences between the young and aged Chinese rice wine. 39 It was also reported that benzaldehyde was one of the most important aroma aldehydes in Proso Millet wine, 43 as a type of traditional Chinese yellow wine.…”
Section: Aldehydes and Ketonesmentioning
confidence: 98%
“…These six compounds are lipid oxidation products derived from linoleic acid and oleic acid, and they have also been detected in Chinese steamed bread as well as cooked cereal grains. 6,10‐dimethyl‐5,9‐undecadien‐2‐one (floral odour) is produced from carotenoid cleavage and is also an important compound in the Japanese green tea . Benzeneacetaldehyde is dominant in proso millet wine, as well as the raw materials .…”
Section: Resultsmentioning
confidence: 99%
“…6,10-dimethyl-5,9-undecadien-2-one (floral odour) is produced from carotenoid cleavage and is also an important compound in the Japanese green tea. 35 Benzeneacetaldehyde is dominant in proso millet wine, as well as the raw materials. 36 Decanal has the character of citrus flavour and is extracted from sweet orange oil.…”
Section: Odour Activity Values Of Quinoa Porridgementioning
confidence: 99%
“…The microbes on/in the grain may even generate special compounds by interacting with the grains, which may lead to special volatiles. The OP released some volatiles (2‐heptanone, 2‐undecanone, 1‐methyl‐naphthalene, and biphenyl) that are related to wine odor (Feng et al., ; Liu et al., ), and it could be that the fermentation occurred with oat grains, which requires further experiments to test.…”
Section: Resultsmentioning
confidence: 99%